Anorexia, bulimia, and obesity: Shared decision making deficits on the Iowa Gambling Task (IGT). - HEVEY, DAVID THOMAS (Cambridge University Press, 2010)
The pathological eating behaviors in Anorexia Nervosa (AN), Bulimia Nervosa (BN), and obesity are characterized by a preference for high immediate reward, despite higher future losses in terms of both physical and psychological outcomes. The present study compared the decision making profile of females with a diagnosis of AN (n = 22), BN (n = 17), obesity (n = 18), and a healthy weight comparison group (n = 20) using a standardized neuropsychological test, the Iowa Gambling Task (IGT). The three clinical groups (AN, BN, obesity) were significantly impaired on the IGT compared with the comparison group on both overall task performance and task learning; however, the three clinical groups were not significantly different from each other. Sixty-one percent to 77% of the clinical groups reached the threshold for impairment on the IGT, compared with 15% of the comparison group. The potential basis for this shared decision making profile is discussed. (JINS, 2010, 16, 711?715.)
PUBLISHED
Keywords: Psychology; Eating disorders